2017
DOI: 10.1016/j.ijom.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography evaluation of midpalatal suture maturation in adults

Abstract: The aim of this study was to evaluate midpalatal suture maturation in adults, as observed in cone beam computed tomography (CBCT) images. CBCT scans from 78 subjects (64 female and 14 male, age range from 18 to 66 years) were evaluated. Midpalatal suture maturation was verified on the central cross-sectional axial slice in the superior-inferior dimension of the palate, using methods validated previously. Intra-examiner agreement was analyzed by weighted kappa test. Multinomial logistic regression was used to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 28 publications
4
53
1
4
Order By: Relevance
“…Our findings are consistent with those of Korbmacher et al 16 who showed that the extent of interdigitation of the MPS was independent of chronological age. Similarly, Angelieri et al 23 and Haghanifar et al 24 showed that chronological age is not a statistically significant predictor of the MPS maturation stage.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings are consistent with those of Korbmacher et al 16 who showed that the extent of interdigitation of the MPS was independent of chronological age. Similarly, Angelieri et al 23 and Haghanifar et al 24 showed that chronological age is not a statistically significant predictor of the MPS maturation stage.…”
Section: Discussionmentioning
confidence: 93%
“…To classify, the evaluators used morphological parameters described in previous studies. 4,10,12 The ability to accompany the palatine anatomy and maintain equidistance from the buccal and nasal cortical bones are the main characteristics that distinguish this proposed method from the original method published. 4 To demonstrate these differences, the sagittal and axial cuts of a same patient To verify the reliability of the method used to classify the palatine suture maturation "status", all images were again evaluated by a second examiner (FG), to obtain the interexaminer error, and 42 images were again evaluated after 30 days by the first evaluator to determine intra-examiner error.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 In this method cone-beam computed tomography (CBCT) scans are applied in order to classify the MPS stage of maturation, and it seems to correlate well with clinical reports. 4,[10][11][12] Nevertheless, some controversies still remain and require clarification.…”
Section: Introductionmentioning
confidence: 99%
“…En conclusión, la expansión rápida maxilar asistida con microimplantes podría ser una alternativa más para solucionar problemas de deficiencia transversal maxilar en especial en pacientes adultos jóvenes. sutura media palatina a través de un corte tomográfico axial para tomar una decisión clínica entre la expansión maxilar rápida y la expansión maxilar rápida asistida quirúrgicamente para el tratamiento de la atresia maxilar en adultos 3,4 . Estas investigaciones describen cinco etapas, ordenándolas en A, B, C, D y E; cada una de ellas está en relación con la resistencia que ofrece la sutura a su separación.…”
Section: Cirugía Oral Y Maxilofacialunclassified